Sosialisasi dan Pelatihan Pembuatan Biogas Dari Limbah Organik Feses Sapi Pada Kelompok Wanita Tani Annisa di Nagari Aripan Kabupaten Solok - Harissatria Harissatria; Dara Surtina; John Hendri; Alfian Asri; Mardianto Mardianto; Delsi Afrini; Edi Firnando; Friza Elinda (LPPM Politeknik Piksi Ganesha, 2026)
The increasing demand for energy necessitates the development of alternative energy sources that are sustainable and environmentally friendly. One potential renewable energy source that can be developed is biogas, produced from livestock waste, particularly cow manure. This community service program aimed to enhance the knowledge and skills of the Annisa Women Farmers Group in Nagari Aripan, Solok Regency, in utilizing cow manure as an alternative household energy source. The methods implemented included socialization, training, discussions, and hands-on assistance in constructing small-scale biogas reactors using one-cubic-meter water tank digesters. The results showed an improvement in participants’ understanding and active participation regarding the concept, benefits, and techniques of biogas production. In addition to producing an alternative energy source that replaces LPG, the by-product of the fermentation process (slurry) was also utilized as an economically valuable organic fertilizer. This activity proved effective in reducing dependence on fossil fuels while promoting sustainable livestock waste management.